2015
DOI: 10.1039/c4sm02292k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of length and rigidity of microtubules on the size of ring-shaped assemblies obtained through active self-organization

Abstract: The microtubule (MT)-kinesin biomolecular motor system has attracted much attention due to its possible applications in artificial biomachines. Recently an active self-organization (AcSO) method has been established to integrate MT filaments into highly organized assembled structures. The ring-shaped MT assembly, one of the structures derived from the AcSO of MTs, can convert the translational motion of MTs into rotational motion. Due to this attractive feature, the ring-shaped MT assembly appears to be a prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
3
27
1
Order By: Relevance
“…The difference in nucleotides between MT-2 (GMPCPP) and MT-4 (GTP) agrees with a common understanding: GMPCPP produces stiffer MTs than GTP due to the conformational change in the tubulin dimers, which is a fact that is supported by all prior experiments. 24,30,31,[50][51][52][53][54][55] However, we found that tau proteins did not show any effect on Lp in our study, different from previous studies. Hawkins et al reported that copolymerizing tau at 1:100 (tau:tubulin) increased Lp (0.6 mm to 4 mm), and Felgner et al reported that adding tau to polymerized MTs increased Lp with the increase of tau (0.92 mm to 2.5 mm).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The difference in nucleotides between MT-2 (GMPCPP) and MT-4 (GTP) agrees with a common understanding: GMPCPP produces stiffer MTs than GTP due to the conformational change in the tubulin dimers, which is a fact that is supported by all prior experiments. 24,30,31,[50][51][52][53][54][55] However, we found that tau proteins did not show any effect on Lp in our study, different from previous studies. Hawkins et al reported that copolymerizing tau at 1:100 (tau:tubulin) increased Lp (0.6 mm to 4 mm), and Felgner et al reported that adding tau to polymerized MTs increased Lp with the increase of tau (0.92 mm to 2.5 mm).…”
Section: Discussioncontrasting
confidence: 99%
“…The difference in nucleotides between MT-2 (GMPCPP) and MT-4 (GTP) agrees with a common understanding: GMPCPP produces stiffer MTs than GTP due to the conformational change in the tubulin dimers, which is a fact that is supported by all prior experiments. 24,30,31,[51][52][53][54][55][56] However, we found that tau proteins did not show any effect on 25,31 This inconsistency is likely due to the growth rate differences between our work and prior work. All our data with tau present was polymerized very slowly and each type (MT-1,2,3,4) showed higher Lp (8.3-17 mm) likely due to this very low growth rate.…”
Section: Discussionmentioning
confidence: 55%
“…We have previously found that the swarming mode of MTs is controlled by the rigidity and length of the MTs 48 , 49 . We prepared MTs with lower rigidity by polymerizing MTs with guanosine triphosphate (GTP) guanylyl-(α,β)-methylene-disphosphonate (GMPCPP) used in the experiments described above 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Even if some of the active probes suffer from any defect, there are sufficient probes available to help characterize the surface mechanical deformation without compromising with the accuracy of measurement. Properties such as the length and rigidity of the probes are also easily tunable 32 33 which in turn would widen the application of the probes. Compared with other methods such as speckle pattern measurement 34 or photoelasticity measurement of materials 35 36 , our method allows direct visualization of direction of surface deformation of soft materials by separating it from internal deformation of the materials.…”
Section: Discussionmentioning
confidence: 99%